Praktik Rukun Qauli Dalam Salat Bagi Difabel Wicara Perspektif Abu Hanifah dan Asy-Syafi’i - Fa'izah, Shofa Auliya (UIN Sunan Kalijaga Yogyakarta, 2022)
In Fiqh, there is no sufficient discussion about the prayer of the speech disabled. Even though there is no specific and detailed discussion regarding the law of prayer for speech disabled people (pillars that cannot be carried out by speech disabled people). In this case there is a difference of opinion between Abu Hanifah and ash-Shafi'i. The type of research used is Library Research, which uses literature in the form of books, books, journals, dictionaries, literature related to the object of study. The nature of this research is descriptive, comparative, analytic, namely explaining, explaining, and analyzing as well as comparing the legal istinbath method used by two jurists. The results of this study indicate that Abu Hanifah and asy Syafi'i have different opinions regarding the pillars of qauli in carrying out prayers. In this case, Abu Hanifah is of the opinion that surah al-Fatihah is not included in the pillars of prayer, but what is included in the pillars of prayer is reading the verses of the Qur'an, if the mushalli cannot read it, then the substitute/badal, the mushalli may replace it by being silent for a moment if during the reading of Surah Al Fatihah finished. Meanwhile, ash-Shafi'i has a different opinion that reading surah al-Fatihah is one of the pillars of prayer, if the mushalli cannot read it, then the substitute/badal, the mushalli may read the surahs that he can whose letters are not less than the number of letters in sura al-Fatihah.